2011
DOI: 10.1016/j.compmedimag.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for detection of pigment network in dermoscopic images using graphs

Abstract: a b s t r a c tWe describe a novel approach to detect and visualize pigment network structures in dermoscopic images, based on the fact that the edges of pigment network structures form cyclic graphs which can be automatically detected and analyzed. First we perform a pre-processing step of image enhancement and edge detection. The resulting binary edge image is converted to a graph and the defined feature patterns are extracted by finding cyclic subgraphs corresponding to skin texture structures. We filtered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Even so, being the reticular pattern (detection, identification or characterization) the main goal of all works, it is worth to look for ways to comparison, among the offered information. Concerning accuracy, Anantha et al (2004) obtained 80% andSadeghi et al (2011) 93%. In contrast, in Leo et al (2010), regarding atypical network, the accuracy values were not shown, but Sensitivity and Specificity are 80% and 82% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, being the reticular pattern (detection, identification or characterization) the main goal of all works, it is worth to look for ways to comparison, among the offered information. Concerning accuracy, Anantha et al (2004) obtained 80% andSadeghi et al (2011) 93%. In contrast, in Leo et al (2010), regarding atypical network, the accuracy values were not shown, but Sensitivity and Specificity are 80% and 82% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In these works, most of the algorithms carry out an automatic segmentation of the lesion, followed by the calculation of features such as color, texture and shape characteristics. In the following, an automatic learning algorithm is applied to select the most discriminant features, enabling the automatic classification (Anantha et al, 2004;Arroyo and Zapirain, 2014;Barata et al, 2012;Betta et al, 2006;Fleming et al, 1998;Grana et al, 2006;Leo et al, 2010;Sadeghi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Structural techniques designed to search for primitive structures such as points, lines and circles, have been extensively adopted for automatically detecting texture and/or local networks in dermoscopic images. Among these: a feature extraction based on the Laplacian of Gaussian (LOG) filtering [20], and the vessel enhancement filter, also known as Frangi's Filter [21].…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…Those features are: globules, dots, pigmented network, streaks, bluewhite veil, and regression. While pigmented network is the most common challenge to be tackled [8,9], nevertheless features like globules need to be detected as well in order to perform in detail analysis of dermoscopic image. In research performed so far on globules detection [10] it is proven that it is possible to detect the feature using Otsu thresholding algorithm.…”
Section: -Dermoscopic Structuresmentioning
confidence: 99%